Genomic Insight into Vibrio Isolates from Fresh Raw Mussels and Ready-to-Eat Stuffed Mussels - Yibar, Artun; Duman, Muhammed; Ay, Hilal; Ajmi, Nihed; Tasci, Gorkem; Gurler, Fatma; Guler, Sabire; Morick, Danny; Saticioglu, Izzet Burcin (MDPI, 2025)
Consuming raw or undercooked mussels can lead to gastroenteritis and septicemia due to Vibrio contamination. This study analyzed the prevalence, density, species diversity, and molecular traits of Vibrio spp. in 48 fresh raw wild mussels (FRMs) and 48 ready-to-eat stuffed mussels (RTE-SMs) through genome analysis, assessing health risks. The results showed Vibrio prevalence rates of 12.5% in FRMs and 4.2% in RTE-SMs, with V. alginolyticus as the most common species (46.7%). It was determined that the seasonal distribution of Vibrio spp. prevalence in the samples was higher in the summer months. The genome sizes of the Vibrio spp. ranged from approximately 3.9 to 6.1 Mb, with the GC contents varying between 41.9% and 50.4%. A total of 22 virulence factor (VF) classes and up to six antimicrobial resistance (AMR) genes were detected in different Vibrio species. The presence of nine different biosynthetic gene clusters (BGCs), 27 prophage regions, and eight CRISPR/Cas systems in 15 Vibrio strains provides information about their potential pathogenicity, survival strategies, and adaptation to different habitats. Overall, this study provides a comprehensive understanding of the genomic diversity of Vibrio spp. isolated from FRM and RTE-SM samples, shedding light on the prevalence, pathogenicity, and toxicity mechanisms of Vibrio-induced gastroenteritis.
Keywords: whole-genome sequencing; foodborne pathogen; mussel; public health; Vibrio spp.; ANTIBIOTIC-RESISTANCE; CULTURED SHRIMP; EFFLUX PUMPS; CLASSIFICATION; INFECTION; OWENSII; GENES; FISH; NOV.; AIR; Microbiology